Погребение кочевника 2-й пол.VII в. у села Черноморское - Комар, А.В.; Орлов, Р.С. (Інститут археології НАН України, 2006)
The paper presents the intake nomad burial 11 of barrow 1 near Chernomorskoie village at Tendrovsk bay, the Black Sea littoral. The burial was made in a pit with little steps and is supplemented by a horse skin folded on the grave overlap, a modelled pot at the head, a knife, a fire steel and also by silver parts of a composite belt of the 3rd quarter of the VII c.